2011
DOI: 10.1016/j.aquaculture.2011.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Type 1 Ostreid Herpes variant (OsHV-1 μvar) with no associated mortality in French-origin Pacific cupped oyster Crassostrea gigas farmed in Italy

Abstract: In April 2010, the sampling of juvenile Pacific cupped oysters originating from France was undertaken from a farm located off the coast of the Marche region in Italy. Samples were sent to the national reference laboratory for mollusc diseases for bacteriological, histological, electron microscopical and molecular analysis. Classical and Real-Time PCR indicated the presence of the microvariant (OsHV-1 μvar) of Type 1 Ostreid Herpes virus (OsHV-1) despite the absence of clinical and pathological signs normally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 10 publications
2
29
0
2
Order By: Relevance
“…These observations mean that from October 2012 until 21 st January 2013, OsHV-1 virus was present in the Hawkesbury River while the environmental conditions were apparently favourable (water temperature above the limit of 16-17°C, data not shown) without leading to significant mortalities. This is in accordance with similar reports from the Netherlands, Spain (EFSA, 2010), Italy (Dundon et al, 2011), Republic of Ireland (Peeler et al, 2012), France (Pernet et al, 2012) and Australia (Paul-Pont et al, 2013b) and confirms that the presence of OsHV-1 is necessary but not sufficient to induce the disease (i.e. mortality).…”
Section: First Detection Of Oshv-1 and Associated Mortalitiessupporting
confidence: 80%
See 1 more Smart Citation
“…These observations mean that from October 2012 until 21 st January 2013, OsHV-1 virus was present in the Hawkesbury River while the environmental conditions were apparently favourable (water temperature above the limit of 16-17°C, data not shown) without leading to significant mortalities. This is in accordance with similar reports from the Netherlands, Spain (EFSA, 2010), Italy (Dundon et al, 2011), Republic of Ireland (Peeler et al, 2012), France (Pernet et al, 2012) and Australia (Paul-Pont et al, 2013b) and confirms that the presence of OsHV-1 is necessary but not sufficient to induce the disease (i.e. mortality).…”
Section: First Detection Of Oshv-1 and Associated Mortalitiessupporting
confidence: 80%
“…Many reports suggest the role of water temperature and the presence of some pathogenic Vibrio species in/prior to the onset of the disease (Burge et al 2007, Sauvage et al 2009, Saulnier et al 2011). However, several field studies have reported an absence of mortality in areas where OsHV-1 and apparently favourable water temperatures were recorded (Dundon et al, 2011;Pernet et al, 2012;Paul-Pont et al, 2013a), suggesting the existence of other underlying environmental factors which may trigger the disease outbreaks. In Europe and New Zealand, movements of oysters or equipment from infected areas appeared to have played a major role in the spread of the disease between geographically distant areas (Bingham et al, 2013;Peeler et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly severe Crassostrea gigas mortalities reported in France, the United Kingdom and the Republic of Ireland in 2008 to 2009 were associated with the presence of an OsHV-1 variant known as the microvariant (µ-var) (Segarra et al 2010). However, recent studies demonstrate that OsHV-1 µ-var can also be detected in asymptomatic oysters, possibly reflecting latent infection or a low viral load (Dundon et al 2011).…”
Section: Introductionmentioning
confidence: 93%
“…Its genome was completely sequenced (13), and the virus was classified as Ostreid herpesvirus 1 (OsHV-1) within the family Malacoherpesviridae (14,15). Moreover, since 2008, mass mortality outbreaks among Pacific cupped oysters have been reported in Europe, including France, Ireland, the Channel Islands, and the United Kingdom (16)(17)(18)(19)(20)(21)(22)(23), in relation to the detection of a particular genotype of OsHV-1 called Var (24).…”
mentioning
confidence: 99%